Ultrasonic studies of the hydration of amino acids and oligopeptides - JUSZKIEWICZ, A. (Archives of Acoustics, 1990)
Hydration number of selected amino acids, their hydrochlorides and their oligopeptides with glycine were determined by the ultrasonic method. Assuming additivity of contributions of ionic and non-ionic groups to the total hydration of the studied substances, the hydration numbers of the free amino acids were calculated. The results obtained are interpreted on the basis of the pseudocrystalline model of water structure.